Genotyping Pattern among Iranian HCV Positive Patients - M Hajia; AA Amirzargar; H Khedmat; N Shahrokhi; M Farzanehkhah; SM Ghorishi; S Biglari; AR Salehinodeh; A Sarafnejad (Tehran University of Medical Sciences, 2010)
Background: Successful treatment to eliminate HCV RNA depends on the identified genotype. In the present study, we compared the frequency of different HCV genotypes, during four years study (2004 till 2008).  Methods: Sera specimens were received from 16 provinces of Iran. We used High Pure Viral Nucleic Acid Purification kit for extraction and samples were tested with improved form of RT-PCR technique. HCV genotypes were determined using Amplisense PCR kit and Amplicor HCV Monitoring Version 2 test utilized a reverse transcription (RT)-PCR approach to quantitative HCV RNA. Two hundreds six HCV positive specimens were entered to the study out of 389 tested samples. Results: Type 3a was the most frequent type (46.6%), followed by type 1 (including 1a and 1b with 25.73% and 17.47% for each respectively) with 43.2%. Looking through collected results of the four years study confirmed the rate of HCV infection in those single genotypes 1b, 3a were slightly increased from 12.22% and 38.88% in the first year to 18.66 and 46.51% in the fourth year of the study period. Conclusion: The analyzed data proved that some patients were infected with two different types.  High viral load was also more correlated to genotype 1 than other types.